A geodetic study of Otago: results of the central Otago deformation network 2004–2014. Issue 1 (2nd January 2016) - Denys, P; Pearson, C; Norris, R; Denham, M
ABSTRACT: We have analysed 11 years of geodetic data from 30 stations distributed over the Otago Fault System in the South Island of New Zealand. Velocities were estimated from time series corrected for coseismic displacements from the 2004 Macquarie Island and 2007 George Sound earthquakes and the coseismic and the short term postseismic deformation associated with the 2009 Dusky Sound earthquake. By dividing the corrected time series in half we were able to demonstrate the existence of a systematic difference between the pre- and post-earthquake velocity fields, associated with a longer term viscoelastic transient related to the 2009 Dusky Sound earthquake. In the northern part of our study area, the geodetic strain rate data are consistent with elastic strain accumulation on the Alpine Fault while in the south and east, the strain rate tensors are consistent with the Otago Fault System. There is a significant change in orientation in the axis of contraction from east to west across the network that correlates with a transition between the Otago and Waihemo Fault Systems. We also demonstrate significant spatial variation in the rates of strain accumulation that may correlate with active and quiescent parts of the Otago Fault System. However these strain rates represent the average values for the 11 years that the COD network has been observed and may also be influenced by the longer term viscoelastic transient related to the Dusky Sound earthquake.